Telling Stories and Creating Participatory Audience: Deep Listening in a Feminist Popular Theatre Project - Shauna Butterwick; Jan Selman (Adult Education Research Conference, 2000)
Combining the understandings of popular theatre as praxis, with feminist scholarship on the struggles and power within the various women’s movements, this paper reports on a community-based project which has created new opportunities for story telling and listening. Through this initiative, different understandings about creating coalitions for social justice have developed.